The Effect of Progressive Muscle Relaxation Technique on Blood Pressure in Hypertension Patients at the Johar Baru District Health Center, Jakarta - AdhijayaPendit, Saka; Dayuningsih, Dayuningsih; Rizqi, Alif Andhika (JOURNAL EDUCATIONAL OF NURSING(JEN), 2023)
Hypertension is a condition where there is an abnormal increase in blood pressure in a person. The impact of hypertension if left untreated can cause visual impairment, nerve disorders, heart failure, and others. Treatment for hypertension can be done by limiting salt intake, doing various activities such as jogging and also using non-pharmacological techniques, namely progressive muscle relaxation techniques. The aim is to determine the effect of Progressive Muscle Relaxation Techniques on reducing blood pressure in patients with hypertension. The method used is descriptive with a nursing process approach including observation, interviews, physical examinations and the application of progressive muscle relaxation techniques to Mr. Y's foster family, especially Mr. Y with hypertension. The results of this case study showed that the application of progressive muscle relaxation therapy for 5 days with a duration of 10 minutes can lower blood pressure. The conclusion of this case study shows that the application of progressive muscle relaxation therapy has been proven to lower blood pressure in patients with hypertension.